The Relationship between the Perception of Emotionally Significant Events in one's Life and World Assumptions of the Student Youth during the Period of Transitive Changes - O.S. Markina; S.V. Molchanov (Психолого-педагогические исследования)
The work is aimed to study the features of the identified emotionally significant events in lives by students in the modern transitive Russian society. The results of an empirical study conducted on Russian students in the period November-December 2022 are presented. The study (N=176) involved respondents aged 19 to 22 years (M=19,9; SD=0,47), citizens of the Russian Federation, students of Moscow universities, of which 79% were girls and 21% were boys. We used a scale of world assumptions of the individual and a questionnaire about emotionally significant events that occurred in a person's life over the past year. The most frequently named categories of events were identified: the spheres of entertainment and leisure, educational and professional activities, and romantic relationships. The results obtained made it possible to highlight the significant basic beliefs of the individual – "positive self-image", "belief in luck" and "belief in control". The nature of the relationship between the basic beliefs of the individual and the identified emotionally significant events is determined. Gender differences in the nature of these emotionally significant events are described.